Joseph Pérez, Los Judíos en España, Madrid, Marcia! Pons Historia, 2005, 357 págs - Rodríguez de Monteagudo, María Concepción (2006)
Fil: Rodríguez de Monteagudo, María Concepción. Universidad de Morón; Argentina